Biological fermentation pretreatment accelerated the depolymerization of straw fiber and its mechanical properties as raw material for mulch film. (15th February 2021) - Sun, Enhui; Zhang, Yue; Yong, Cheng; Qu, Ping; Huang, Hongying; Xu, Yueding
Abstract: In order to reduce the negative ecological effects and environmental pollution caused by large-scale herbicide application in rice cultivation, a straw fiber mulch film (FMF) was developed. This study applied high-temperature enzymatic solution technology as a pretreatment process for rice straw (RS) fibers, causing beneficial physicochemical structural changes. Chemical composition, crystallinity index (CrI), degree of polymerization (DP), thermal stability, and other parameters of deconstructed RS fibers were analyzed. The change in CrI showed that appropriate pretreatment times can improve crystallinity, while excessively long pretreatment times caused crystallinity to sharply decrease from 44.65 wt% to 41.34 wt%. The CO bonds between lignin and hemicellulose were almost completely destroyed, confirming the deconstruction of linkages within RS fibers, making the material significantly softer and looser. Compared with untreated straw fibers, the mechanical pulping beating time decreased significantly, reducing energy consumption by 43.75%. The FMFs prepared with appropriate fermenting times exhibited improved mechanical properties. The tensile strength of FMF prepared using biological pretreatment fermentation (BPF) as a raw material increased from 11.26 N m g −1 to 15.68 N m g −1, exhibiting an increase of 39.25% compared to traditional fermentation (TF). This work provides a novel method, which has the potential to effectively control herbicides and support the development of sustainable agricultural systems. Graphical abstract: Schematic diagram of straw fiber biological deconstruction and pulping for the production of mulch films. Image 1 Highlights: Biological fermentation pretreatment accelerated depolymerization of straw fiber. Fiber biological fermentation for 12 d reduced beating energy requirements. Treated straw mulch film has potential for sustainable agricultural application.